Agronomic potential of new seedless grapes grafted on rootstocks for Southern Brazil - Feldberg , Nelson Pires; Silva, Giovani Olegário da; Biasi, Luiz Antonio (Pesquisa Agropecuaria Brasileira, 2025)
The objective of this work was to evaluate the phenology, productive performance, plant vigor, and fruit physicochemical characteristics of three white seedless grape cultivars, recently introduced into Brazil, when grafted on the main rootstocks used in the Southern region of country, during two crop seasons. The experiment was carried out in a randomized complete block design, in a 2×3×4 factorial arrangement (crop seasons×cultivars×rootstocks). The used cultivars were Neptune, Hope, and Gratitude, and the rootstocks were Paulsen 1103, VR 043-43, IAC 572, and IAC 766. Neptune was the first cultivar to be harvested, on January 27, followed by Hope, on January 31, and by Gratitude, on February 15. Sprouting and harvest occurred earlier (2 to 7 days and 2 to 3 days, respectively) on 'IAC 766' and later (2 to 5 days and 2 to 3 days, respectively) on 'VR 043-43'. In addition, plants grafted on 'IAC 572' were more vigorous. The three evaluated cultivars showed a high total soluble solids/total titratable acidity ratio, varying from 24.96 to 49.22. However, the three cultivars present different responses regarding phenological stages, yield, plant vigor, and fruit physicochemical characteristics in both crop seasons when grafted on the Paulsen 1103, VR 043-43, IAC 572, and IAC 766 rootstocks.
Keywords: Vitis spp.; adaptation; phenology; table grapes; viticulture